Optimalisasi Program P4GN BNN Kota Surabaya Melalui Media Digital - Ikrimah Tsuraya; Dwi Setianingsih (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Drug abuse is a crucial issue that has a significant impact on various segments of society. In this regard, the Surabaya City National Narcotics Agency (BNN) utilizes digital platforms as part of its public communication strategy to support the implementation of the Drug Prevention, Eradication, Abuse, and Illicit Trafficking (P4GN) Program. This study aims to evaluate the extent to which the Surabaya National Narcotics Agency (BNNK) optimizes the use of digital media, while identifying the obstacles faced and the strategies implemented. Using a qualitative descriptive approach, data was collected through interviews, observation, and documentation of the digital activities carried out by the Surabaya National Narcotics Agency (BNNK). The research findings indicate that social media such as Instagram, TikTok, YouTube, X, and Facebook have been actively utilized to disseminate educational content and anti-drug campaigns. However, the use of digital media still faces challenges such as limited human resources, limited budgets, the digital literacy gap, and a lack of two-way interaction with users. To address these challenges, the Surabaya City BNN implemented various strategies, including internal training, collaboration with influencers, and active employee involvement in the content dissemination process. This optimization effort is a strategic step in increasing collective public awareness of the dangers of drugs through a more responsive, inclusive, and sustainable digital communication approach.